Advances in the in situ analysis of reactive oxygen species (ROS) - Szelągowska, Maja; Skrzypek, Justyna; Gawlik, Maciej (Farmacja Polska, 2021)
In recent years, a particular increase in interest in the subject of reactive oxygen species (ROS) has been observed. ROS are produced in cells under physiological conditions, but in the event of an oxidative imbalance, an increase in their concentration adversely affects the functioning of the body. Free radical ROS are compounds that contain oxygen atoms with an unpaired electron. These ROS include the superoxide anion radical and the hydroxyl radical. ROS that do not have an unpaired electron are singlet oxygen, ozone and hydrogen peroxide. As a result of the imbalance between ROS generation and antioxidant defence, oxidative stress (OS) arises. It contributes to the damage of DNA and proteins, causes lipid peroxidation, destruction of the cell membrane and, as a result, loss of cell integrity and function, apoptosis and necrosis. These processes are the basis for the development of most civilization diseases, such as atherosclerosis, arterial hypertension, cancer and neurodegenerative diseases. The critical impact of these disorders on basic vital functions emphasizes the importance of monitoring ROS levels at the place of their formation (in situ). Precise knowledge about the actual production of ROS opens up wider possibilities of diagnosing the above-mentioned diseases. It allows to determine their genesis, predict the direction of their development and to improve the treatment process. There are many methods for determining ROS, unfortunately none is completely perfect. Difficulties in the diagnosis of ROS are caused by their high reactivity and low durability. The article describes the techniques that allow for the precise determination of ROS. These include chemiluminescence, fluorescence, near infrared fluorescence, Amplex Red, immunohistochemical methods, electron spin resonance or Frequency Mixing Magnetic Detection (FMMD) There is a need to invent a method that will enable quick, non-invasive and reliable determination of ROS, which in turn will contribute to the improvement of the diagnostic process of many diseases.